Soft X-ray holographic microscopy of chromosomes with high aspect ratio pinholes - Barth, Ruth; Staier, Florian; Simpson, Todd; Mittler, Silvia; Eisebitt, Stefan; Grunze, Michael; Rosenhahn, Axel (Journal of biotechnology, 2010)
We used digital in-line soft X-ray holography (DIXH) in the Gabor geometry to image human chromosomes. The divergent wave front was generated by diffraction of synchrotron radiation from a high aspect ratio pinhole. As under our experimental conditions the achievable resolution depends on the pinhole radius, high aspect ratio holes with diameters in the 100nm range were prepared by focused ion beam (FIB) milling. The central maximum of the obtained Airy pattern was used to image chromosomes prepared from metaphase HeLa cells at experimental resolutions of 370±40nm with soft X-rays at 260eV photon energy provided by the BESSY II synchrotron radiation facility.